2011
DOI: 10.4103/0971-5851.92813
|View full text |Cite
|
Sign up to set email alerts
|

How common is hypothyroidism after external radiotherapy to neck in head and neck cancer patients?

Abstract: Purpose:To identify the occurrence of clinical and subclinical hypothyroidism among head and neck cancer patients receiving radiation to the neck and to justify routine performing of thyroid function tests during follow-up.Materials and Methods:This is a prospective nonrandomized study of 45 patients of head and neck cancer, receiving radiotherapy (RT). Thyroid stimulating hormone and T4 estimations were done at baseline and at 4 months and 9 months following RT.Results:Of the 45 patients, 37(82.2 %) were male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…12,25,26 Only Tell et al 17 found that increasing age was correlated with an increased risk of hypothyroidism. In a study by Srikantia et al, 27 52.9% of the patients who developed clinical hypothyroidism were between the age groups of 51 to 60 years. In our study, the occurrence was definitely higher in patients older than 45 years of age.…”
Section: Discussionmentioning
confidence: 90%
“…12,25,26 Only Tell et al 17 found that increasing age was correlated with an increased risk of hypothyroidism. In a study by Srikantia et al, 27 52.9% of the patients who developed clinical hypothyroidism were between the age groups of 51 to 60 years. In our study, the occurrence was definitely higher in patients older than 45 years of age.…”
Section: Discussionmentioning
confidence: 90%
“…[ 11 ] Development of clinical hypothyroidism occurs at a rate of about 5 to 20% per year. [ 12 ] Clinical hypothyroidism typically manifests by slow mentation, depression, dry skin, pleural and pericardial effusions, decreased gastrointestinal motility, weight gain, cold intolerance, chronic fatigue, congestive heart failure, decreased wound healing and acceleration of atherosclerosis. [ 9 ] None of our patients had any of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Srikantia et al . found that[ 12 ] 52.9% of the patients developing clinical hypothyroidism were 51 to 60 years old. ( P = 0.0522); however, the mean patient age analysed were in the range of 52 years.…”
Section: Discussionmentioning
confidence: 99%
“…, disfunção faringo-laríngea (disfagia e aspiração, 25%), hipotireoidismo (42%), ototoxicidade (27%), fístula/necrose cutânea (29%) e osteorradionecrose (4%) (33,34) .…”
Section: Segundo Dados Do Projeto Globocan Da International Agency Forunclassified
“…O tempo para o desenvolvimento do hipotireoidismo é variável mas considera-se um intervalo mediano de 1,4 a 1,8 anos, com variação de 0,3-7,2 anos (83)(84)(85) e estima-se uma incidência entre 7,2-53% ao longo de 3 a 5 anos de seguimento (34,(82)(83)(84)(86)(87)(88)(89)(90)(91) . Uma revisão sistemática da literatura que avaliou 971 pacientes, a maioria deles tendo sido irradiada para CECCP, encontrou uma incidência de hipotireoidismo subclínico de 26 a 53% e de hipotireoidismo de 11 a 33% (92) .…”
Section: Hipotireoidismounclassified